Crossing the bridge: foreign language students’ reciprocal images in (inter)cultural mediation between Portugal and Turkey - Basílio, Daniel (2016)
This study intends to highlight the role that Foreign Language Education (FLE), particularly in the Higher Education context, can play so as to contribute to the rapprochement of two distant and still mutually unknown countries such as Portugal and Turkey. In this sense, it ultimately aims at supporting the training of intercultural speakers, capable of promoting an effective Intercultural Dialogue between the two countries. A diagnosis is presented of the reciprocal images of Portuguese and Turkish students learning each other's language and culture. Conclusions are drawn on how their self- and hetero-images may pertain on the construction of their identities, on their awareness about and attitudes towards each other, on their motivation to learn each other's language, and on intercultural communication itself. Allying the study of Images of Languages and Cultures and the concept of Intercultural Competence in the study of students’ representations within the FLE research tradition, a content analysis was carried out of the responses given to an inquiry by questionnaire. Conative implications of the students’ images as revealed in the results were pointed out. Some important distinctions are highlighted in the reciprocal images of both groups. On this basis, recommendations for FLE are made focusing on the positive reconstruction of students’ reciprocal images.